A Deed So Accursed : Lynching in Mississippi and South Carolina, 1881-1940 - Finnegan, Terence, 1961- (Book collections on Project MUSE., 2013)
From the end of Reconstruction to the onset of the civil rights era, lynching was prevalent in developing and frontier regions that had a dynamic and fluid African American population. Focusing on Mississippi and South Carolina because of the high proportion of African Americans in each state during "the age of lynching," the author explains lynching as a consequence of the revolution in social relations - assertiveness, competition, and tension - that resulted from emancipation.